The influence of attitude, subjective norms, and perceived behavioral control on vaccination intention among teachers: The moderating role of perceived policy effectiveness - Noor Amira Syazwani, Abd Rahman; Ju, Soon-Yew; Jamal Rizal, Razali; Mohd Rozaimy, Ridzuan; Kong, Lai-Kuan (Universiti Sultan Zainal Abidin, 2024)
Background and Purpose: This study explores teachers' influence on families' vaccination decisions and the role of schools in health education. It aims to identify factors shaping teachers' attitudes toward vaccines and their decision-making when vaccinating their children. Using the Theory of Planned Behavior, the research examines educators' attitudes, subjective norms, and perceived behavior control about vaccination choices. It provides insights into the crucial role of schools and teachers in promoting vaccination and enhancing vaccine acceptance in society. Methodology: A quantitative approach was employed to analyze the data in this study. Questionnaires were distributed to teachers in three states in Malaysia, namely Pahang, Terengganu, and Kelantan. Out of the total 400 questionnaires distributed, only 326 were found suitable for analysis after the screening process. The data were then analyzed using the partial least square structural equation modeling (PLS-SEM) method. Findings: The study reveals a significant link between teachers' attitudes toward vaccinating children and a connection between subjective norms and parents' vaccination intentions. These findings support previous research, underscoring the influence of attitudes and subjective norms on vaccination decisions. However, no significant relationship was found between perceived behavior control and parents' intention to vaccinate, suggesting that parents' beliefs about accessing vaccines or overcoming barriers have a limited impact on their vaccination intentions. In addition, Perceived policy effectiveness positively influenced parents' vaccination intentions. Contributions: This study enhances understanding teachers' vaccination intentions, informing evidence-based policies to promote vaccination and address barriers. Recognizing the factors influencing teachers' decision-making, targeted interventions can enhance vaccination rates and improve public health outcomes.